2015
DOI: 10.1172/jci80275
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of PKG1α oxidation augments cardioprotection in the stressed heart

Abstract: B r i e f r e p o r t 2 4 6 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 27 publications
6
72
0
Order By: Relevance
“…Consequently, it is possible that scenario-specific localization of PKG I␣ occurs depending on the subcellular source of cGMP or oxidant, as well as the amounts of each generated. Indeed, it is notable that the ability of PKG I␣ to form a disulfide dimer impacts on its subcellular localization in cardiac myocytes in response to exogenous hydrogen peroxide or those from transaortic constriction (TAC)-stressed hearts (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is possible that scenario-specific localization of PKG I␣ occurs depending on the subcellular source of cGMP or oxidant, as well as the amounts of each generated. Indeed, it is notable that the ability of PKG I␣ to form a disulfide dimer impacts on its subcellular localization in cardiac myocytes in response to exogenous hydrogen peroxide or those from transaortic constriction (TAC)-stressed hearts (11).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the zipper in PKG I␣ is integral to the protection that elevation in cGMP by PDE5 inhibitors can provide, and this is because it enables the kinase to bind and phospho-activate RhoA, which ultimately limits apoptosis. The C42S PKG I␣ KI mice are also innately resistant to TAC-induced cardiac dysfunction (11). The disulfide in PKG I␣ occurs between Cys-42 residues directly within the leucine zipper domain required for targeting of the kinase to RhoA.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, oxidation has been shown to increase the in vitro interaction between PKGI␣ and two of its interacting proteins, RhoA and MYPT1 (12). In addition, a recent paper by Nakamura et al (15) demonstrated that the C43S mutation appeared to alter PKGI␣ subcellular localization in cardiac myocytes, which suggests a change in association of with interacting/anchoring proteins in cells, but the structural basis for oxidation-induced changes in these interactions was not examined. We are currently pursuing these studies.…”
Section: Pkgi␣ Is Not Activated By Cysmentioning
confidence: 99%
“…19,22,23,50 Mouse models of pressure overload-induced hypertrophy/remodeling showed that protein kinase G and GC1 activity is downregulated and that the localization of GCb1 is directly disrupted. 6,51 We observed significant hypertrophy compared with WT in all studied groups ( Figure S8), but no other obvious structural damage was seen (not shown). Conversely, cGMP is a negative regulator of the cardiac hypertrophy-related remodeling process, 52 and it was recently shown that stimulation of GC1 activity protects from pathological remodeling and heart failure after myocardial infarction.…”
Section: Potential Function Of the Cx43-gc1 Associationmentioning
confidence: 80%
“…In humans and animals subjected to a prolonged state of cardiac hypertrophy, the initial compensatory mechanisms and their failure lead to maladaptive structural remodeling associated with decreased Cx43 assembly in GJs at the ID and increased Cx43 membrane lateralization 19, 22, 23, 50. Mouse models of pressure overload–induced hypertrophy/remodeling showed that protein kinase G and GC1 activity is downregulated and that the localization of GCβ1 is directly disrupted 6, 51. We observed significant hypertrophy compared with WT in all studied groups (Figure S8), but no other obvious structural damage was seen (not shown).…”
Section: Discussionmentioning
confidence: 99%